Hyperglycemia among hospitalized cancer patients with coexisting diabetes mellitus. (November 2015) - Karlin, Nina J; Cheng, Meng-Ru; Castro, Janna C; Cook, Curtiss B
Aims: The objective was to study the care of hospitalized patients with diabetes mellitus and coexisting cancer.Patients & methods: Hospitalized patients with a new solid organ malignancy and diabetes were retrospectively analyzed. Multivariable generalized estimating equation models evaluated associations between cancer type and hyperglycemia (glucose >180 mg/dl).Results: Among 443 patients with 914 hospitalizations, cancer types included prostatic, liver, lung, kidney, pancreatic, bladder, breast, colorectal and gynecologic. Increased hemoglobin A1c (β = 2.72; p < 0.01), mean glucose within 24 h after admission (β = 0.27; p < 0.01) and insulin administration (β = 10.16; p < 0.01) were significantly associated with hyperglycemia. No association existed between cancer type and hyperglycemia frequency (p = 0.79).Conclusion: Inpatient hyperglycemia management is not associated with type of solid organ malignancy.